Preliminary evidence of an effect of cerebellar volume on postural sway in FMR1 premutation males. (25th March 2015) - Birch, R. C.; Hocking, D. R.; Cornish, K. M.; Menant, J. C.; Georgiou‐Karistianis, N.; Godler, D. E.; Wen, W.; Hackett, A.; Rogers, C.; Trollor, J. N.
Abstract : Recent evidence suggests that early changes in postural control may be discernible among females with premutation expansions (55–200 CGG repeats) of the fragile X mental retardation 1 ( FMR1 ) gene at risk of developing fragile X‐associated tremor ataxia syndrome (FXTAS). Cerebellar dysfunction is well described in males and females with FXTAS, yet the interrelationships between cerebellar volume, CGG repeat length, FMR1 messenger RNA (mRNA) levels and changes in postural control remain unknown. This study examined postural sway during standing in a cohort of 22 males with the FMR1 premutation (ages 26–80) and 24 matched controls (ages 26–77). The influence of cerebellar volume, CGG repeat length and FMR1 mRNA levels on postural sway was explored using multiple linear regression. The results provide preliminary evidence that increasing CGG repeat length and decreasing cerebellar volume were associated with greater postural sway among premutation males. The relationship between CGG repeat length and postural sway was mediated by a negative association between CGG repeat size and cerebellar volume. While FMR1 mRNA levels were significantly elevated in the premutation group and correlated with CGG repeat length, FMR1 mRNA levels were not significantly associated with postural sway scores. These findings show for the first time that greater postural sway among males with the FMR1 premutation may reflect CGG repeat‐mediated disruption in vulnerable cerebellar circuits implicated in postural control. However, longitudinal studies in larger samples are required to confirm whether the relationships between cerebellar volume, CGG repeat length and postural sway indicate greater risk for neurological decline. Abstract : Cerebellar volume as a mediator of the effect of CGG repeat length on postural sway in FMR1 premutation males.